Zirconia-Hydroxyapatite Composite Coating on Cp-Ti Implants by Biomimetic Method - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2012)
Hydroxyapatite (HA) is the major component of the natural hard tissues such as teeth and bone. It has been studied extensively as a candidate biomaterial for its use in prosthetic applications. However, the main weakness of this material lies in its poor mechanical strength which makes it unsuitable for load-bearing applications. On the other hand zirconia (ZrO2) powder has been widely studied because of its high strength and fracture toughness and good biocompatibility. Therefore, the addition of zirconia phase into HA will improve the mechanical properties and biocompatibility of HA ceramics. The present study focused on coating of HA-ZrO2 on commercially pure titanium (cp-Ti) using novel biomimetic sol-gel method. The HA-ZrO2 coatings produced with BSG method were exhibited highly crystalline and pure structure. The coating thickness of the samples was not significantly influenced by the change in gelatin concentration and volume. It was concluded that the suggested coating method is a useful method to produce a biomimetic coating layer on the cp-Ti sample surfaces.
Keywords: Dip-coating; Sol-gel; Biomimetic; Zirconia-Hydroxyapatite composite; cp-Ti; CALCIUM HYDROXYAPATITE; TITANIUM